Utilisation of Ablution Water with Nano Technology for Integrated Water Spinach and Fish Cultivation System at As-Salafiyyah Asy-Syafi'iyyah Islamic Boarding School - Nasirudin, Mohamad; Ciptadi, Gatot; Agung Pramana Warih Marhendra; Maharani Pertiwi K.; Juwita Ratna Dewi; Ardyah Ramadhina Irsanti Putri; Septian Ragil Anandita; Agus Suhadi; Gladys Agnescia Sumampouw (Jurnal Pembangunan dan Alam Lestari, 2026)
The objective of this study is to develop and evaluate strategies for the utilisation of nano technology-based ablution water waste in integrated farming systems comprising catfish, tilapia, gourami, iridescent shark, and water spinach. Utilising an interdisciplinary approach, this study not only examines the effectiveness of water treatment technology, but also seeks to empower pesantren human resources to achieve technical and economic independence. The novelty of this research lies in the integration of nanotechnology-based water treatment technology, the utilisation of the results for productive cultivation, and the empowerment of human resources in the Islamic boarding school community. This research was conducted at the As-Salafiyyah Asy-Syafi'iyyah Tambakberas Barat Islamic Boarding School, Jombang, East Java, from August to October 2025. The findings of the study demonstrate that the integration of electrocoagulation, zeolite-based nanofiltration, and ozonation technologies is efficacious in enhancing the quality of ablution wastewater. This assertion is substantiated by a substantial decline in pollutant parameters, specifically: The BOD decreased from 78 mg/L to 24 mg/L, with an efficiency of 69.2%, the COD decreased from 39 mg/L to 17 mg/L, with an efficiency of 56.4%, and the TSS decreased from 76 mg/L to 25 mg/L, with an efficiency of 67.1%. The utilisation of treated water as a cultivation medium yielded favourable outcomes, manifesting in the accelerated growth of water spinach plants. A notable augmentation in plant length was observed, escalating from 10.2 centimetres at seven days post-planting to 39.8 centimetres at 28 days after planting. Concurrently, the number of leaves increased from 9 at 7 days after planting to 38 leaves at 28 days after planting. Furthermore, the fresh weight of the plants exhibited a substantial increase, rising from 3 grams at seven days after planting to 37 grams at 28 days after planting. Furthermore, treated water has been demonstrated to support the growth of various fish species, including patin, tilapia, gurami, and catfish. The fastest growth was exhibited by tilapia and catfish, reaching 27 g and 18 g at 28 days after planting, respectively, with a final length of 14.83 cm and 13.25 cm, respectively. The present study will examine the level of technology acceptance among Islamic boarding schools. Keywords: Nanotechnology, Ablution Wastewater, Aquaculture, Hydroponics, Islamic Boarding School